That someone guilty be punished : the impact of the ICTY in Bosnia - Orentlicher, Diane; Open Society Justice Initiative; International Center for Transitional Justice (New York, N.Y. : Open Society Justice Initiative ; International Center for Transitional Justice, 2010)
"When the United Nations Security Council established the International Criminal Tribunal for the former Yugoslavia (ICTY) in May 1993, expectations were low. War was still raging in the Balkans, and the creation of the Tribunal was perceived as an attempt by Security Council members to save face after failing to stanch the violence then wracking the region. Few could have foreseen the deep and lasting effects of the ICTY on Bosnia and Herzegovina, the Balkans, and international law. What began as an ad hoc response to the war's atrocities set a precedent that marked the beginning of the post-Nuremberg era of international justice: since the ICTY's founding, the international community has established courts to address atrocities committed in Rwanda, Sierra Leone, Cambodia, Kosovo, and Timor Leste, as well as a permanent International Criminal Court with more than 100 states parties. The ICTY has also directly contributed to national war crimes prosecutions, both in Bosnia and Herzegovina, and throughout the region. Moreover, the ICTY has created a rich jurisprudence of international humanitarian law that now informs the work of other national and international courts. In That Someone Guilty Be Punished, Diane F. Orentlicher, professor of law at American University, looks at the effects and effectiveness of the ICTY, including lessons to improve future efforts to provide justice for survivors of atrocious crimes. Perhaps most importantly, Orentlicher examines the impact of the tribunal through the words and experiences of those in whose name it was established: the victims and survivors. Their expectations, hopes, and disappointments are chronicled alongside the tribunal's achievements and limitations. Based on hundreds of hours of interviews--and featuring the voices and perceptions of dozens of Bosnian interlocutors--That Someone Guilty Be Punished provides a comprehensive and complex portrait of the ICTY and its impact on Bosnia."--Page 4 of cover.
Acknowledgments -- Methodology -- Introduction -- Background -- Victims' justice -- Achievements, failures, and performance --
Truth and acknowledgment -- Impact on domestic war crimes prosecutions -- Notes.
HU OSA 207 - Donation of the Open Society Institute-Budapest
Keywords: International Tribunal for the Prosecution of Persons Responsible for Serious Violations of International Humanitarian Law Committed in the Territory of the Former Yugoslavia since 1991.; War crimes -- Bosnia and Herzegovina; War crime trials -- Bosnia and Herzegovina